2010
DOI: 10.3892/ol_00000064
|View full text |Cite
|
Sign up to set email alerts
|

α(1,2)fucosylation in human colorectal carcinoma

Abstract: Abstract. lewis b and lewis y (le) antigens are known to be elevated in colorectal tumours. Alterations in the catalytic behaviour of gDP-l-fucose:β-D-galactoside α(1,2) fucosyltransferase [α(1,2)Ft, ec: 2.4.1.69], the key enzyme in their synthesis, have been suggested as being responsible for these changes. In particular, an aberrant tumour-specific α(1,2)Ft activity that converts le a and le x to le b and le y determinants, respectively, has been reported in colorectal cancer tissues. to clarify the catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Of the ten carbohydrate building blocks, alpha-l-fucose seems a critically important pathological effector (Miyoshi et al, 2008;Muinelo-Romay et al, 2011;Wu et al, 2012). In particular, over-expression of alpha2-fucosylated epitopes is reported to be associated with tumor cell phenotypes from multiple tissues, including pancreas (Takiyama et al, 1988), endometrium (Ambros and Kurman, 1993) and colon (Sun et al, 1995;Muinelo-Romay et al, 2010), and down-regulation of fucosyltransferase FUT1 is reported to impair angiogenesis in vitro (Moheler et al, 2008) and to inhibit tumor growth (Zhang et al, 2008). More specifically, alpha2-fucosylated glycans have been indicated as responsible for influencing cell motility and resistance to apoptosis in CD44 variants (Goupille et al, 2000) as well as for regulating functions of nucleolin in CVEC, including those involved in proliferation (Aldi et al, 2009;Palumberi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Of the ten carbohydrate building blocks, alpha-l-fucose seems a critically important pathological effector (Miyoshi et al, 2008;Muinelo-Romay et al, 2011;Wu et al, 2012). In particular, over-expression of alpha2-fucosylated epitopes is reported to be associated with tumor cell phenotypes from multiple tissues, including pancreas (Takiyama et al, 1988), endometrium (Ambros and Kurman, 1993) and colon (Sun et al, 1995;Muinelo-Romay et al, 2010), and down-regulation of fucosyltransferase FUT1 is reported to impair angiogenesis in vitro (Moheler et al, 2008) and to inhibit tumor growth (Zhang et al, 2008). More specifically, alpha2-fucosylated glycans have been indicated as responsible for influencing cell motility and resistance to apoptosis in CD44 variants (Goupille et al, 2000) as well as for regulating functions of nucleolin in CVEC, including those involved in proliferation (Aldi et al, 2009;Palumberi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In CRC, qualitative, quantitative and distributive differences in the expression of glycoconjugates between adenocarcinoma - derived tissue and normal mucosa are well known [6–8]. Among these changes, increased fucosylation has been described and related with malignant transformation, invasion and metastasis [7,9,10]. Fucosylation is influenced by several factors, including the levels and activities of the enzymes involved, the levels of GDP-fucose and other monosaccharide-nucleotides and the transport of these substrates across the membranes of the endoplasmic reticulum and Golgi apparatus.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of colon Le b (and Le y ) antigen is completed by other a(1,2)FT, which directly fucosylates Le a to Le b (and Le x to Le y ) (13). The genetic origin of this a(1,2) FT remains uncertain, but all evidence suggests that both activities are associated with the FUT3 gene encoding the a(1,3/4)FT or Lewis enzyme (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…In sum, a) changes in H and Lewis antigen expression in colorectal carcinogenesis have been documented; b) the synthesis of these fucosylated determinants requires several tissue-specific FT acting on core 1 and core 2 precursors; and c) the kinetic alterations of some of these enzymes in CRC have recently been reported by our laboratory (13). Despite this background, contradictory data remain, and new insights in this field are required.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation